ANALISIS KREDIT BERMASALAH PADA BANK “X” PERIODE 2007-2010 - Marwansyah, Sofyan (www.bsi.ac.id, 2013)
Banks play an important role in the economy because banks can promote the growth and development especially in the economic field. In carrying out its function as an intermediary institution should optimize the lending bank to its customers. However, loans granted by the bank did not rule out the risk, and therefore an analysis needs to be done so we can figure out how to set up a bank lending. Based on the details of non-performing loans (NPL) in table III.1, III.2, III.3 Where the average - average non-performing loans (NPL) Bank